2022
DOI: 10.1155/2022/5363754
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Letrozole Combined with Urinary Gonadotropin for Ovulation Induction in Endocrine Abnormal Infertility Patients: A Retrospective Single-Center, Case-Control Study

Abstract: Aims. To ask lots of questions and try to find the truth about the medicine-based effectiveness of letrozole (LE) combined with human menopausal gonadotropin (HMG) in the treatment of inability to have children crops patients with endocrine (things that are different from what is usually expected and the effect on ovulation-related chemicals produced by the body). Materials and Methods. A total of 160 unable to have children crops patients with endocrine things that are different from what is usually expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Medical interventions for unexplained infertility with genetic factors include medications to address hormonal imbalances. Hormonal imbalances affect ovulation and sperm production, with ovulation-stimulating medications like clomiphene citrate and letrozole for women and gonadotropins for men [117,118].…”
Section: Lifestyle Changes and Medical Interventions For Genetic Caus...mentioning
confidence: 99%
“…Medical interventions for unexplained infertility with genetic factors include medications to address hormonal imbalances. Hormonal imbalances affect ovulation and sperm production, with ovulation-stimulating medications like clomiphene citrate and letrozole for women and gonadotropins for men [117,118].…”
Section: Lifestyle Changes and Medical Interventions For Genetic Caus...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%